(untitled) (The Pakistan Development Review, 2021)
The current population age structure of Pakistan provides the country an opportunity to reap the demographic dividend but there is no concrete evidence on its magnitude. The National Transfer Accounts (NTA) can fill this gap by quantifying the wealth flows taking place in a population through an improved understanding of the generational economy.2 The NTA provides estimates of people’s income and their consumption at every age. What is more important, however, is that the NTA helps to understand how do people, especially the young and the old who consume more than they produce, support themselves. It sheds light on whether it is through the private or public sources that the existing deficit—the difference between income and consumption—if any is filled. The estimation of the NTA for Pakistan, therefore, would strengthen our understanding of the linkages between population dynamics and development. The NTA for Pakistan provides the opportunity to look at the economic indicators through the perspective of age. It can help design public policies ranging from healthcare, education, gender equality, reproductive health and social protection to economic, social and political implications of population ageing and generational equity.